Practical do-it-yourself device for tissue expander procedures [Doku genişletici uygulamalari için yeni ve pratik bir yöntem] - (:unkn) unknown (My University, 2011)
Tissue expansion is one of the most frequently used modalities in plastic surgery but the manipulation of the expander volume during the operation remains to be a very exhausting and time consuming action. A simple and useful method with a practical do-it-yourself device is presented here to improve the comfort of the surgeon and decrease the duration of this manipulation.